2007
DOI: 10.1007/s00018-007-6452-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of steroid hormone signaling pathway in insect cell differentiation

Abstract: To dissect the steroid hormone signaling pathway involved in insect cell morphological differentiation, we extended the application of the double-stranded RNA-mediated interference (dsRNAi) method to the epidermal IAL-PID2 cell line from Plodia interpunctella Lepidoptera. We first demonstrated that dsRNA was capable of efficiently blocking the steroid hormone 20-hydroxyecdysone (20E) inducibility of proteins that belong to the nuclear receptor superfamily, including the ecdysone receptor (EcR), its partner Ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…Therefore, our RNAi results provided evidence for the involvement of EcR-B1, USP-2 and HR3 in a 20E signalling pathway that induces G2/M arrest of imaginal cells by regulating B cylin expression. It is known that the G2/M arrest of IAL-PID2 cells is followed by a morphological differentiation with the formation of cytoplasmic extensions accompanied by an increased synthesis of b tubulin (Siaussat et al, 2007). Other recent RNAi experiments have demonstrated that the silencing of EcR-B1, USP-2 and HR3 prevented the 20E effects on the b tubulin and the shape of IAL-PID2 cells (Siaussat et al, 2007).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Therefore, our RNAi results provided evidence for the involvement of EcR-B1, USP-2 and HR3 in a 20E signalling pathway that induces G2/M arrest of imaginal cells by regulating B cylin expression. It is known that the G2/M arrest of IAL-PID2 cells is followed by a morphological differentiation with the formation of cytoplasmic extensions accompanied by an increased synthesis of b tubulin (Siaussat et al, 2007). Other recent RNAi experiments have demonstrated that the silencing of EcR-B1, USP-2 and HR3 prevented the 20E effects on the b tubulin and the shape of IAL-PID2 cells (Siaussat et al, 2007).…”
Section: Discussionmentioning
confidence: 97%
“…The dsRNAs were stored at À20 1C for several months. For RNAi experiments, the preparation of dsRNA-Lipofectamine 2000 complexes and the transfection into IAL-PID2 cells are described by Siaussat et al (2007).…”
Section: Preparation Of Double-stranded Rna (Dsrna) and Dsrna Interfementioning
confidence: 99%
See 1 more Smart Citation
“…It is proposed that the resistance mechanism exists at the junction between the conserved ecdysone regulatory cascade and the differentiation program in the cell line. RNAi studies in IAL-PID2 cells have con fi rmed the involvement of the ecdysone regulatory cascade in cell cycle arrest and morphological transformation (Siaussat et al 2007(Siaussat et al , 2008 .…”
Section: Use Of Cell Lines To Detect Resistance Mechanisms To Insectimentioning
confidence: 99%
“…Other assays employed organ cultures to evaluate molting hormone activity such as those based on the evagination of imaginal discs (Smagghe et al 2000 ) and the promotion of chitin synthesis by cuticle fragments (Nakagawa et al 1998 ;review by Nakagawa 2005 ) . Insect cell lines generally respond to ecdysteroids and non-steroidal ecdysone agonists by cessation of cell proliferation and formation of fi lamentous extensions (Wing 1988 ;Sohi et al 1995 ;Siaussat et al 2007 ;Mosallanejad et al 2008 ) and this property has indeed been exploited for development of screening systems for ecdysone analogs (e.g. the B II bioassay; Dinan et al 2001 ;Harmatha et al 2002 ) .…”
Section: Cell-based Screening Assaysmentioning
confidence: 99%